PENGEMBANGAN GAME EDUKASI KARTU AKSI BAIK VS BURUK DENGAN MODEL 4D UNTUK MENANAMKAN PERILAKU RAMAH LINGKUNGAN TERKAIT PERUBAHAN IKLIM PADA SISWA KELAS 4 SD DI PKBM EDUHOUSE SEMARANG - Wahyu Sudrajat, Andy; Zulfikasari, Sony (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental education regarding climate change at PKBM EduHouse Semarang faces significant challenges due to the lack of interactive learning media and gadget distractions that hinder student focus. This study aims to develop a valid and practical physical learning media in the form of the